2016
DOI: 10.1016/j.cllc.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Features Are Associated With EGFR Mutation Status in Lung Adenocarcinomas

Abstract: Background This study retrospectively evaluated the capability of computed-tomography (CT) based radiomic features to predict EGFR mutation status in surgically-resected peripheral lung adenocarcinomas in an Asian cohort of patients. Materials and Methods 298 patients with surgically resected peripheral lung adenocarcinomas were investigated in this institutional review board-approved retrospective study with waived consent. 219 quantitative 3D features were extracted from segmented volumes of each tumor, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
255
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(272 citation statements)
references
References 39 publications
11
255
5
1
Order By: Relevance
“…Few studies have investigated associations between the tumor imaging phenotype and the underlying molecular landscape (2431,33). These studies generally had small sample sizes, used subjective observer-dependent imaging descriptors, and did not perform robust external validation.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated associations between the tumor imaging phenotype and the underlying molecular landscape (2431,33). These studies generally had small sample sizes, used subjective observer-dependent imaging descriptors, and did not perform robust external validation.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT imaging data have also been adopted to predict clinical endpoints, such as overall/disease-free survival [15], local/distant recurrence [16], and distant metastasis [17]. Radiomic features are associated with epidermal growth factor receptor mutation status in lung adenocarcinomas [18], and the biological basis of radiomic features have also been explored in the view of molecular pathways in lung cancer [19]. Moreover, the combination of radiomic features and genetic biomarkers could boost the prediction performance for predicting tumor recurrence in stage I NSCLC patients [20].…”
mentioning
confidence: 99%
“…Several studies have suggested the use of DWT‐based decomposed images for the calculation of radiomic features . Aerts et al.…”
Section: Introductionmentioning
confidence: 99%